ANALYSIS OF DENTIGEROUS CYST, AMELOBLASTOMA, AND ODONTOGENIC KERATOCYST PANORAMIC RADIOGRAPH AND CBCT: A SCOPING REVIEW - Monica Siregar; Suhardjo Sitam; Yurika Ambar Lita; Indra Hadikrishna (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: The radiographic images similarity of a dentigerous cyst, ameloblastoma, and odontogenic keratocyst can lead to misdiagnosis. The radiographic images of these lesions can be analyzed using panoramic radiographs and CBCT with quantitative and qualitative methods of analysis. The purpose of this study was to find out what radiographic methods is better to used on panoramic radiograph and cbct to analysis these lesions so that the diagnose could be more objective, to determine the characteristics of these lesions, and to determine the use of CBCT and panoramic radiography in establishing radiodiagnosis of these lesions.Method: This research was conducted using a scoping review, through searching for articles related to the research topic in Pubmed, EBSCOHost, and Google Scholar. Result: Fifty-eight studies and case reports were reviewed in this study. This study analyzed these lesions using quantitative methods based on buccolingual size, density, and lesion volume using CBCT. Qualitative methods were used to analyze border and shapes, associations, internal structures, and locations using panoramic radiography and CBCT. Based on the cases studied, size, border, and shape of these lesions were the least optimal characteristics analyzed by panoramic radiography and CBCT.Conclusion: Ameloblastoma has a higher incidence of multilocular forms than OKC and dentigerous cysts and causes tooth resorption, while dentigerous cysts often cause tooth displacement. CBCT can be a gold standard in analyzing dentigerous cyst, ameloblastoma, and odontogenic keratocyst. Analysis of CBCT images could be more objective because it can be carried out using quantitative methods for calculating the density, volume, and size of the buccolingual expansion. Based on the case reports reviewed, size, border, and shape are the least used in determining suspected radiodiagnosis.